KASIH SAYANG KELUARGA PERSPEKTIF ASMA’ AL-HUSNA Implementasi Makna Ar-Rahmān, Ar-Rahīm, Al-Wadūd, Ar-Ra`ūf dan Al-Latīf dalam Keluarga Islami - Saifuddin, Warto (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2020)
This paper aims to explore the meaning of asma’ al-ḥusna in connection with affection, love, tenderness and grace, so that Muslims can implement it in married life. A family is built for the purpose of obtaining happiness, peace, tranquility, comfort, tranquility, wholeness and togetherness. Meanwhile, love is the foundation. If a family loses affection, then great disasters and storms will hit the household ark and the fatal impact will be family destruction. For that we need the correct understanding and concept of the meaning of affection in the family. This paper uses a qualitative descriptive method. Data obtained from the Koran, hadith, Islamic books, journals and the internet. The results of the study show that affection has various forms. These variations are based on the similarities of the asma’of Allah Ar-Raḥmān, Ar-Rahīm, Al-Wadūd, Ar-Ra`ūf and Al-Laṭīf. These variations of meaning include general and specific affection, affection which is dominant in spite of hatred, affection which can overcome anger and affection which is able to forgive mistakes. When these variations in the meaning of affection can be implemented in the family, a sacred family that is far from destruction will be realized.